ANALISIS PENGARUH PROMOSI YANG TERINTEGRASI DAN KEUNGGULAN POSITIONING TERHADAP KEPUTUSAN PEMBELIAN SABUN MANDI LUX DI KOTA AMBON - Anggrainy Chaniago; Merry M. Pelupessy; Sarifuddin Sarifuddin; Yulianty S. Ginting (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2020)
The bath soap market is constantly changing and competition is getting tougher with the emergence of bath soaps that have a clearer positioning, such as beauty soap, whitening soap, family soap to health soap. Increasing lifestyles of people in Indonesia and changing habits where bathing is no longer just using soap, but by adding fragrance and comfort when wearing it. The higher purchasing power of consumers for a product encourages companies to further improve the quality of their products. The purpose of this study is to analyze the effect of Integrated Promotion and Positioning Excellence on Purchasing Decisions in Lux Bath Soap. The population in this study are consumers in the city of Ambon who use Lux bath soap. The sample in this studywere 100 people who bought lux bath soap taken by purposive sampling. The data collection is done by using a questionnaire. The data analysis method used is SPSS version 16.The results of multiple regression analysis namely Y = 0.501 X1 + 0.218 X2 The most influential independent variable on the dependent variable is the integrated Promotion variable (0.501), followed by the Positioning Excellence variable (0.218). T test results show that all independent variables, namely (integrated promotion and positioning superiority) have a significant positive effect on the dependent variable (purchasing decisions) where all independent variables obtain a t value greater than t table with a sig level of less than 0.05. And the coefficient of determination (R Square) obtained by 0.309 this means that 30.9% of purchasing decisions can be explained by integrated promotion variables and positioning excellence, while the remaining 69.1% is influenced by other variables not examined in this study. Keywords: Integrated Promotion, Positioning Excellence, Purchasing Decisions